Importancia de la confirmación diagnóstica en el laboratorio de las dermatofitosis en caninos - Rosa, D.E. (2020)
Dermatophytosis (tinea) in canines (Canis lupus familiaris) is a superficial mycosis of cosmopolitan distribution. The most common causative agents are Microsporum canis and Nannizzia gypsea, these dermatophyte fungi are capable of parasitizing the keratinized tissues of man and animals. The agreement between the clinical diagnosis and the laboratory diagnosis of these superficial mycoses causes controversies, since according to other authors, it varies between 10.2 % and 38.7 % of the cases reported. The objective of this work was to confirm, by conventional techniques of the Mycology laboratory, the clinical diagnosis of dermatophytosis generated by Veterinarians. Between 2011 and 2016, 106 samples of canine skin of both sexes were studied. The canines were between 2 months to 17 years of age. In the laboratory of Mycology, 27.3 % of the clinical diagnoses were confirmed. 62 % of dermatophytosis were caused by Nannizzia gypsea and 32 % by Microsporum canis. 7.5 % of the patients were positive for Demodex canis although the clinical diagnosis was dermatophytosis. The errors in the clinical diagnosis generate false positives with the consequent over estimation of the incidence in addition to the therapeutic failure.